Identification of a Rare and Potential Pathogenic MC4R Variant in a Brazilian Patient With Adulthood-Onset Severe Obesity - Salum, Kaio Cezar Rodrigues; de Souza, Guilherme Orofino; Abreu, Gabriella de Medeiros; Campos Junior, Mário; Kohlrausch, Fabiana Barzotto; Carneiro, João Regis Ivar; Nogueira Neto, José Firmino; Magno, Fernanda Cristina C. Mattos; Rosado, Eliane Lopes; Palhinha, Lohanna; Maya-Monteiro, Clarissa Menezes; Cabello, Giselda Maria Kalil de; et al. (Frontiers in Genetics, 2020)
Background: The melanocortinergic pathway orchestrates the energy homeostasis and impairments in this system often lead to an increase in body weight. Rare variants in the melanocortin 4 receptor (MC4R) gene resulting in partial or complete loss of function have been described with autosomal co-dominant inheritance. These mutations are the most common cause of non-syndromic monogenic obesity. In this context, this study aimed to sequence the MC4R gene in a Brazilian cohort of adults with severe obesity. Methods: This study included 320 unrelated probands with Body Mass Index (BMI) ≥ 35 kg/m², stratified into three groups, according to the period of obesity onset. From the total sample, 122 patients were enrolled in the childhood-onset group (0 – 11 years), 79 patients in the adolescence/youth-onset group (12 – 21 years), and 119 patients in the adult-onset group (> 21 years). Blood pressure, anthropometric and biochemical characteristics were obtained, and the MC4R coding region of each subject’s DNA was assessed using automated Sanger sequencing. Results: Significant anthropometric differences between the groups were observed. Higher body weight and BMI medians were found in patients with childhood-onset or adolescence/youth-onset when compared to the adulthood-onset obesity group. A total of seven mutations were identified, including five missense variants: p.Ser36Thr, p.Val103Ile, p.Ala175Thr, p.Phe202Leu, and p.Ile251Leu. Additionally, we observed one synonymous (p.Ile198=) and one start lost mutation (p.Met1?). The p.Ala175Thr variant was identified in a female case with severe obesity and adulthood-onset. This variant was previously described as a partial loss-of-function mutation, in which the minor allele poses dominant-negative effect, probably resulting in reduced cAMP activity. Conclusion: This study showed a prevalence of common and rare variants in a cohort of Brazilian adults with severe obesity and candidates to bariatric surgery. We have identified a rare potentially pathogenic MC4R variant in a Brazilian patient with severe and adulthood-onset obesity.